Green tea peptides ameliorate diabetic nephropathy by inhibiting the TGF-β/Smad signaling pathway in mice. Issue 6 (2nd March 2022) - Chen, Xuhui; Sun, Lingli; Li, Dongli; Lai, Xingfei; Wen, Shuai; Chen, Ruohong; Zhang, Zhenbiao; Li, Qiuhua; Sun, Shili
Abstract : Diabetic nephropathy (DN) is the most important cause of middle and late-stage chronic kidney disease. Abstract : Diabetic nephropathy (DN) is the most important cause of middle and late-stage chronic kidney disease. Green tea polypeptides are extracted from tea pomace, and exhibit various pharmacological effects. In this study, we analyzed the reno-protective effects of green tea peptides in diabetic db/db mice, and explored the underlying mechanisms. Peptide treatment for 5 weeks significantly reduced the blood glucose levels and other indices of diabetes, and alleviated renal injury measured in terms of blood creatinine, urea nitrogen and urinary albumin/urinary creatinine levels. Mechanistically, the green tea peptides downregulated p-Smad2/3, α-SMA, ZO-1 and vimentin proteins in the kidney tissues, and elevated Smad7. Thus, green tea peptides inhibited the deposition of ECM proteins by suppressing excessive activation of the TGF-β/Smad signaling pathway and reducing fibronectin levels. On the other hand, tea peptides ameliorated renal injury by inhibiting the production of inflammatory factors (iNOS and TNF-α) by suppressing the NF-κB signaling pathway. In addition, we confirmed the inhibitory effect of green tea peptides on the TGF-β/Smad signaling pathway in TGF-β1-stimulated HK-2 cells. Therefore, tea peptides can be considered as an effective candidate for alleviating DN.